The Winners and the Losers: Tax Incidence of Gambling in Finland - Tomi Roukka; Anne H. Salonen (Springer, 2022)
Gambling markets have grown rapidly for the last few decades. As a result, gambling is also a very important and common source of tax income for many governments these days. This raises a question about the overall fairness of the gambling taxation systems. In this paper, we aim to study the tax incidence of gambling in Finland. First, we analyse who are the expected payers of the gambling taxes and second, who are expected to be the receivers of the gambling-tax based contributions. In the first part of the study, we analyse the demographic incidence of gambling taxation by using the Finnish gambling 2015 population survey combined with registry based variables. Our data contains 3776 individuals. In the second part of the study, we use data of county level gambling-taxation based contributions to different organisations to analyse how the gambling expenditures are distributed back to citizens in a form of public spending. This study shows that different socio-demographic factors have diverse association with the decisions whether or how much to gamble. The results also suggest that more disadvantaged, i.e. lower income, less educated and rural area living, individuals are expected to be the “losers” of the Finnish gambling taxation system. In other words, the Finnish gambling system is found to be regressive by nature.